Market Power and Inflation - Chirinko, Robert S.; Fazzari, Steven M. (The Review of Economics and Statistics, 2000)
Market power exercised by firms has become central to macroeconomics. Recent theoretical work highlights the importance of the relation between market power and inflation. We examine this relation for individual firms in eleven U.S. industries. Our econometric framework exploits restrictions from dynamic theory and information from financial markets to generate quantitative evidence on the responsiveness of market power to inflation. We find that inflation usually has a positive effect on market power. This relation is heterogeneous across the eleven industries, and statistically significant positive relations are concentrated in industries with little market power.